Obligation and consent - Lesser, H. (Journal of medical ethics, 1989)
It is often supposed, as in Professor Kluge's article (1), that one can only acquire an obligation by free consent. This paper argues that although this is true of some types of obligation, including the ones discussed by Professor Kluge, it is by no means true of all. In particular, it is argued, society may legitimately impose obligations on us without our consent, if the obligations are reciprocated, or if it is simply enforcing an already existing moral obligation.